ADAPTASI FAAL TUBUH TERHADAP LATIHAN HATHA YOGA PADA LANSIA PENDERITA HIPERTENSI - Rahima Rahima; Endang Kustiningsih (Universitas Batanghari Jambi, 2017)
The quality of life of the elderly will be preserved through physical activity or sport, because exercise becomes a very physiological stimulus involving all body systems. Proper physical activity and routine for the elderly will be very beneficial for both physical and psychological. Hatha yoga is believed to be an alternative non-pharmacological treatment in lowering blood pressure and some other diseases caused by vascular and metabolic disorders. Therefore with this research is expected to produce a preliminary assessment of how adaptation physiology of the cardiovascular system lungs in elderly against the practice of hatha yoga that is based on facts obtained, able to provide an understanding of the efforts to improve the quality of life of the elderly through physical activity. Methode of research is experimental research design quasi-experimental (Quasi experiment Design) without a control group with the approach of one group pretest-posttest. The sample in this research is the elderly who suffer from hypertension or high blood pressure are a total of 11 people who exercise hatha yoga for 12 weeks on a regular basis with the frequency of exercise three times a week. The results of this study showed changes significant reductions in blood pressure systole and blood pressure diastole in the elderly before and after the practice of hatha yoga, There are changes significant reduction average between Heartbeat elderly before and after the practice of hatha yoga, There is a changes a significant increase on average between frequency of breath just before and after the practice of hatha yoga. The suggestions: Yoga exercises are done in routine can be one of the non-pharmacological therapy in reducing the state hemodynamics mainly on the blood pressure of elderly who suffer from hypertension and the need to do more research on the examination system of immunology and more of the elderly against the practice of hatha yoga, accompanied by a review of the sport in elderly with control and treatment groups in order to obtain more in-depth resultsKeywords: adaptation, exercise, hatha yoga, elderly